Those old familial feelings: transference in reading Thomas Ogden's The Parts Left Out. Issue 11 (1st November 2020) - Mishra Tarc, Aparna
ABSTRACT: A novel can alter a change in readers over a lifetime. This paper examines the dynamics of transference animated by novels that affect us. In her reading of Thomas Ogden's The Parts Left Out, the author follows the novel's aesthetic and formal operation as it animates transference to one's own childhood in readers. The conceptualisation of transference in reading advanced in this paper leans on Melanie Klein's version of the workings of unconscious phantasy in the infant's first felt reading of the (m)other. The content of novels that profoundly affect us, the author argues, aesthetically and formally operate via self-other and/or author-reader transference in the event of reading.